IOT-ENABLED AUTOMATION OF A GEOMETRICALLY OPTIMIZED SMART PADDLEWHEEL AERATOR. - Roy, Suranjit; Kumar, Avinash (Scientific Culture, 2026)
Aquaculture systems face challenges with maintaining dissolved oxygen (DO) levels which result in decreased productivity and create stress for aquatic life while traditional aeration methods waste energy through their ineffective operations. The paper presents an IoT-based geometrically optimized smart paddlewheel aerator which features a real-time monitoring system and an automated controller to achieve oxygen management and energy efficiency. The approach will involve designing an experimental setup using DO temperature and pH sensors which connect to a microcontroller (ESP32/Arduino) and cloud-based monitoring system. The aerator operates automatically according to preset DO limits which control its power state between shutoff at 6mg/L and activation at 4mg/L while the design specifications for blade angle (450 degrees), rotational speed (80-100 RPM), and immersion depth (30-40%) have been optimized to achieve maximum operational efficiency of the aerator. The findings show that the system is accurate and stable with respect to the DO levels (6.12-6.35 mg/L) and stability (1.67 2.08% error). The suggested system improved the DO to 6.8 mg/L versus 5.6 mg/L on conventional methods, and decreased power usage by 32.3% energy saved and enhanced efficiency of 0.0017Wh/ppm, and had a high level of reliability (>97% accuracy, <3 s delay) with the IoT.